The economy of Pompeii - Flohr, Miko; Flohr, Miko; Wilson, Andrew; Wilson, Andrew (Oxford studies on the Roman economy, 2017)
This work addresses, from a variety of perspectives, the economy of the Roman city of Pompeii. It uses archaeological and textual evidence to discuss topics as diverse as agriculture in the fertile plains at the foot of mount Vesuvius, diet and health, manufacturing, urban investment, consumption, trade and money